2020
DOI: 10.1016/j.tre.2020.102064
|View full text |Cite
|
Sign up to set email alerts
|

Trade disruptions, behavioral biases, and social influences: Can luxury sporting goods supply chains be immunized?

Abstract: Highlights A dual channel supply chain with multi-tiered products experiencing trade disruption and market volatility is studied. A flexible trade credit contract with minimum order quantity (MOQ) is devised. A coordination mechanism under social influences and behavioral biases is established. Impacts of trade disruptions, social influences, and loss-aversion on channel coordination are studied.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 52 publications
1
7
0
Order By: Relevance
“…Hoang et al (2022) suggested that organizations should restructure the enterprise's team structure from the traditional e-commerce team to a matrix team that works based on the customers' segments. Asian et al (2020) suggested that luxury products companies, especially luxury sports goods (LSG) companies, should conduct innovation in their supply chain by applying the risk-sharing and coordinating roles of flexible trade credit contracts to generate optimal decisions of wholesalers and LSG suppliers.…”
Section: Online Landscapementioning
confidence: 99%
“…Hoang et al (2022) suggested that organizations should restructure the enterprise's team structure from the traditional e-commerce team to a matrix team that works based on the customers' segments. Asian et al (2020) suggested that luxury products companies, especially luxury sports goods (LSG) companies, should conduct innovation in their supply chain by applying the risk-sharing and coordinating roles of flexible trade credit contracts to generate optimal decisions of wholesalers and LSG suppliers.…”
Section: Online Landscapementioning
confidence: 99%
“…Similarly, the supplied backup and flexible quantity contract allow retailers and wholesalers to handle their inventories effectively. As a result, these contracts have been extensively used to address trade disruption (Asian et al 2020 ; Tavana et al 2019 ) (Asian et al 2020 ; Rahbari et al 2021 ), supply chain sustainability (Chan et al 2018 ; Hajiagha et al 2021 ), and supply chain coordination issues (Lu and Liu 2021 ). While any of these contracts has been beneficial in resolving new supply chain problems, researchers have found that a mixed combination of collaboration contracts allows for a greater understanding of a supply chain model under various coordination contracts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Traceability helps prevent damage to the brand's reputation resulting from counterfeit products or illegal and illegitimate commercialisation (Castelli and Sianesi, 2015;Khan, 2015;Robinson and Hsieh, 2016). It is, however, not easy to achieve the desired levels of traceability in supply chain management because it demands coordination and control over actors and processes (Caniato et al, 2011;Khan, 2015;Asian et al, 2020), which is a big challenge for supply chain operations characterised by the relatively large volume and decentralised channels, i.e. the accessible luxury supply chain.…”
Section: Luxury Supply Chain Managementmentioning
confidence: 99%